The Meccan Umrah: Knowing and Transmitting - AlSiddiqui, Abdulrahman Abdulwahab (Journal of Islamic Sciences, 2020)
This research aims to collect and extrapolate all the hadiths and relics mentioned in the Umrah of Meccan, which support it and contradictory, with its graduation and its degree, then explain the doctrines of scholars and the owners of the four schools, especially in the ruling on Umrah for Meccan, and whoever said of them of its legitimacy and evidence for that, as well as from He said the opposite while explaining the most correct evidence of evidence, and the research also dealt with a statement of the doctrines of the scholars in the meqat of Mecca, and an explanation of the best of it, Afaqi a distinction in all of this between the Meccan, Al-Helly and Al-Afaqy in terms of the terminology of the jurists. All of this is based on an analytical and comparative approach that relies on analyzing the evidence and statements presented in the issue with comparisons between them and stating the similarities and differences between them, Among the most important results of this research: Saying that it is permissible to perform Umrah for Meccan and that it is desirable. And that the meqat of Mecca for Umrah is generally the solution, and that Meccan is a name given to everyone who settles in Mecca.
Keywords: Umrah; Meccan; Hadiths; Al-Athar; Umrah ruling; Miqat